KISAH-KISAH SOSOK HANTU BELANDA DI MASA KOLONIAL DALAM TINJAUAN SEJARAH DAN ISLAM - Ryzky Yan Deriza; Wira Alvio; Arafah Pramasto (Jurnal Studi Islam, 2022)
Ghost stories are an example of Urban Legend which is popular in Indonesia. Some of circulating stories are the ghost figures of the Dutch people in a number of areas. This research uses historical research methods through its stages, namely heuristics, criticism, interpretation, and historiography. The formulation of the problem that will be answered is : How is the historical and Islamic theological views of the ghost stories of the Dutch figure?. This research proves that these stories are residues that remain in the communal memory of the Dutch colonial era. Mr. Ruud “the filthy ghost” in Lawang Sewu stems from the phenomenon of concubinage which is considered morally flawed between European men and non-European women (especially the natives). The ghost stories of Dutch painters and ‘noni’ (lit. ‘Young Girl) at the Kuntskring Building Jakarta are nostalgia for the architectural splendor of colonial heritage. Meanwhile, the ghost of Noni Elisse Rikkar van Eindhoven in Palembang, who liked to seduced and then harmed men, is a critique of gender and racial tendencies towards a free lifestyle among Dutch women. Islam as the religion that is predominantly embraced by the Indonesian people agrees that there are supernatural beings that interfere with humans, namely ‘Jinns’ with the ability to fly, disappear, and resemble humans (except for the Prophet Muhammad), but not because of the ‘Ruh’ or human spirit that has died, because ‘Ruh’ is the business of Allah, however humans have little knowledge about this.Key words: Urban Legend, Dutch Ghost, Colonial, Jin Abstrak: Kisah-kisah hantu merupakan sebuah contoh Legenda Urban yang populer di Indonesia. Beberapa kisah yang beredar adalah sosok-sosok hantu orang Belanda di sejumlah daerah. Riset ini memakai metode penelitian sejarah melalui tahap-tahapnya yakni heuristik, kritik, interpretasi, dan Penyajian (historiografi). Rumusan masalah yang akan dijawab ialah bagaimana tinjauan historis dan teologis keislaman terhadap kisah-kisah hantu sosok orang Belanda tersebut ?. Penelitian ini membuktikan bahwa kisah-kisah itu merupakan residu yang membekas dalam memori komunal mengenai era Kolonial Belanda. Hantu Mr. Ruud yang bejat di Lawang Sewu berakar dari fenomena pergundikan yang dianggap cacat moral antara lelaki Eropa dan wanita Non-Eropa (utamanya kaum pribumi). Cerita hantu para pelukis dan Noni-noni Belanda di Gedung Kuntskring Jakarta ialah nostalgia kemegahan arsitektur warisan kolonial. Sedangkan hantu Noni Elisse Rikkar van Eindhoven di Palembang yang senang menggoda dan mencelakakan laki-laki, merupakan kritik bertendensi gender dan rasial terhadap gaya hidup bebas di kalangan perempuan Belanda. Islam sebagai agama yang mayoritas dipeluk masyarakat Indonesia menyepakati bahwa terdapat makhluk gaib yang mengganggu manusia yakni Jin dengan kemampuan terbang, menghilang, dan menyerupai manusia (terkecuali Rasulullah Saw.), namun bukan disebabkan ruh manusia yang sudah wafat karena hal itu adalah urusan Allah dan manusia hanya memiliki pengetahuan sedikit tentang hal ini. Kata kunci: Legenda Urban, Hantu Belanda, Kolonial, Jin